Criminal Justice in Italy between the End of the Liberal State and Fascism: Transnational Perspectives between the USA and Italy (1919-1945) - Luigi Lacchè (Clio@Themis)
This article considers how American scholars and articles published in English viewed the Italian reforms of Criminal Justice implemented between the “Ferri project” (1919) and the Fascist regime. It analyzes in particular how Fascist criminal reforms have been received, interpreted and assessed from that perspective. To summarize the views of American legal thinkers on Fascist criminal reforms we can say that, despite the popularity of positivism in the U.S. at the turn of the century, the radical Ferri Code was criticized in several respects. By the mid-1930s American responses were still focused on questions of criminal science, rather than the nature of the regime itself. The isolationist policy of the U.S. did not prevent a number of scholars from assessing certain aspects of Fascist codes and criminal reforms, pointing out problems and contradictions. The transnational viewpoint is therefore important to understand better the real nature of the Fascist regime and the formal maintenance of the principle of legality.